Fecal methylated syndecan-2 (SDC2) testing for early screening of colorectal cancerous and precancerous lesions: A real-world retrospective study in China - Boyu Qin; Haitao Niu; Lupeng Qiu; Hongfeng Zhou; Peng Lyu (Cancer Pathogenesis and Therapy)
Background: Colorectal cancer (CRC) is a major public health concern and the second leading cause of cancer-related deaths worldwide. However, challenges remain in deploying effective screening strategies for early-stage CRC. This study aimed to evaluate the effectiveness of a fecal-based syndecan-2 (SDC2) methylation test for the detection of colorectal lesions and CRC. Methods: We retrospectively collected data on participants who underwent fecal SDC2 methylation testing from January 1, 2019, to May 30, 2023. Patients with positive results were recommended to undergo colonoscopy. Performance indicators associated with certain clinical characteristics, including positive rate (PR), positive predictive value (PPV), and colonoscopy compliance rate (CCR), were subjected to statistical analysis. Results: We analyzed data from 113,209 participants, of whom 11,841 (10.4% PR) had positive fecal SDC2 methylation test results. A total of 4315 participants with positive results adhered to the colonoscopy recommendations, and the CCR was 36.4%. Finally, 3169 colorectal lesions were detected, including 1134 polyps, 875 non-advanced adenomas (NAAs), 770 advanced adenomas (AAs), and 390 CRCs, with PPV values of 26.3% (1134/4315), 20.3% (875/4315), 17.8% (770/4315), and 9.0% (390/4315), respectively. Notably, the PPV for CRC increased significantly with age (χ2 = 164.40, P < 0.0001). In addition, as the cycle threshold (CT) values increased, the PPVs of AAs and CRCs generally decreased, whereas those of NAAs and polyps significantly increased. Moreover, the clinical patient group had the highest incidence of late-stage CRC (stage II and higher), whereas asymptomatic populations from the staff physical examination group and rural town-based screening programs had the highest number of stage 0 and I CRCs detected (P = 0.0107). Conclusions: This study indicates that fecal SDC2 methylation testing combined with colonoscopy may be an effective screening method for colorectal lesions and CRC.